The Model of Employee Performance: An Empirical Study - Husainah, Nazifah (Dinasti International Journal of Digital Business Management, 2023)
The performance of employees in the telecommunications industry is a direct result of the tasks assigned to them by the company or organization. Compensation, organizational culture and job satisfaction are considered to play a vital role in influencing employee performance and achievement of stated goals. Although the impact of organizational culture on its members may not be significant, higher pay and job satisfaction are positively associated with higher performance. The purpose of this study is to determine the significant effects of compensation, work culture, and job satisfaction on employee performance. To achieve this, we took a sample of 420 respondents and collected data using a statement questionnaire. Regression analysis was performed on the collected data using SPSS 20.0 for Windows program. Regression analysis results show that salary, job satisfaction, and organizational culture have significant positive and direct effects on employee performance in the telecom industry.